ChemInform Abstract: Palladium‐Catalyzed Direct Amination of Allylic Alcohols at Room Temperature. Issue 19 (May 2015) - Wang, Maorong; Xie, Yinjun; Li, Jiawen; Huang, Hanmin
Abstract: A palladium complex efficiently allows the direct amination of allylic alcohols with amines at room temperature without further additives.